Comparison of conventional sensor with single mode optical fiber sensor for monitoring of partial discharge in oil insulation - Khallawi, Alaa Razzaq (2014)
High-voltage transformer is the most critical and expensive component in a power system network in order to ensure the stability of the system. Partial discharge (PD) is small electrical sparks present in an insulator as result of the electrical breakdown of a gas (for example air) contained within a void or in a highly nonuniform electric field. Partial discharge (PD) phenomenon is one of the reasons that happen in high voltage appliances and lead to failure of power transformer, leading to expensive repair and power outage. An acoustic emission (AE) phenomenon also happens near the discharge zone that is used to detect (PD).Partial discharge detection is a technique widely used for high voltage equipment insulation condition monitoring and assessment. Many researchers have used acoustic emissions (AE) at the vicinity of the discharge zones to detect PD. This project compares the sensitivity of single mode fiber optical sensor with capacitive sensor. The fiber optical sensor (FOS) and capacitive sensor were immersed in an oil tank fitted with two steel electrodes which were connected to different values of high voltage source. The data obtained by both sensors were then analyzed in time and frequency domain, and compared by peak analysis that suggest that single mode optical fiber was able to act as acoustic sensor with large wide band of signals. These experimental results are interesting which also suggest that both sensors have peculiar characteristics for the detection of AE and could be used as per the PD detection requirements.